Characteristics and Shareholder Wealth Effects of Mergers and Acquisitions Involving European Renewable Energy Companies - Mirosław Wasilewski (MDPI AG, 2021)
The present study documents a positive market reaction to mergers and acquisition (M&A) deals involving renewable energy companies. Acquirers record positive post-deal cumulative risk-adjusted returns upon taking over a renewable energy target, especially if the former also operates in the renewable energy sector. Such deals often involve purchases of majority equity stakes financed with acquirers’ stock rather than cash. Acquirers of renewable energy firms tend to be more profitable and cash-rich than their industry peers, yet they are less likely to be serial acquirers and channel cash reserves towards M&As. We evidence that the quality of corporate governance in the energy sector may play a substantial role in shaping the choice of targets; a director’s outside affiliations increase the likelihood of takeovers of non-energy firms, while the presence of outsiders on board appears to incentivize diversification into renewable energy. While acquisitions of renewable energy firms feature lower-than-average acquisition premia and generate positive short-term stock returns, they are found to exercise an overall negative short- and medium-term impact on the combined entities’ operating performance. Overall, capital markets appear to attach a sizeable premium to risky deals involving renewable energy firms, possibly in expectation of wealth accrual in the long term.